Exploitative competition and coexistence in a parasitoid assemblage. Issue 1 (21st September 2012) - Teder, Tiit; Tammaru, Toomas; Kaasik, Ants
Abstract: Most insect populations are exploited by a complex of different parasitoid species, providing ample opportunities for competitive interactions among the latter. Despite this, resource‐mediated competition (i.e., exploitative competition) among insect parasitoids remains poorly documented in natural systems. Here we propose a novel way to infer the presence of competitive interactions from covariance patterns in parasitism levels, and illustrate the use of this approach on a relatively well‐defined and simple host–parasitoid system. The parasitism levels caused by three parasitoid species on a shared host showed a highly consistent negative covariance among samples. With the levels of parasitism by one species increasing, the levels of parasitism attributable to the two others decreased. Importantly, negative covariance between parasitism levels by different species appeared at high abundance, but not at low abundance of the phenologically earlier parasitoid species. This as well as several other lines of evidence indicates the importance of competitive interactions in this system. Feeding biology and phenology of the parasitoids suggest that competition in this parasitoid assemblage is primarily resource‐mediated rather than occurring through direct interference. The species attacking earlier stages of the host are competitively superior to those attacking their host later in the season. Better dispersal ability and use of alternative host species by the inferior species could contribute to the coexistence of these competing parasitoids.